PENDEKATAN MODEL MATEMATIKA SATU DIMENSI PADA SALURAN PENGENDAP PASIR - Imam Suprayogi; Anton Ariyanto (Jurnal APTEK, 2010)
Sandtrap channels are usually found at rivers intake for irrigation purposes. These channel were made to settle sands and prevent them from entering the irrigation channel. As result, the water that enter the irrigation channel will be relatively clean (with small concentration). This objective of this research applying finite different method to solve water flow differential equation as the basis computer`s software construction using Borland Delphi 5 language for sand trap, testing model`s ability against field measurement result, also applying efficiency point and sediment simulation of sandtraps.The analysis of discharge data, flow velocity, water depth, and field measurement result data as basis for total load calculation using Engelund Hansen, Leo Van Rijn, and Enstein Brown formulation approach. The result is using as an input data for sandtrap`s one dimensional empirical model formulation , which was developed by Eysink Vermaas (1983).